Effect of nanoparticles on the morphology and properties of PET/PP in situ microfibrillar reinforced composites. Issue 12 (20th November 2015) - Liu, Ying; Zhao, Zhongguo; Tang, Dahang; Kong, Miqiu; Yang, Qi; Huang, Yajiang; Liao, Xia; Niu, Yanhua
Abstract : In this work, the effect of SiO2 nanoparticles on the morphology and properties of PET/PP in situ microfibrillar reinforced composites (MFC) obtained from slit die extrusion and hot stretching‐quenching was investigated. The scanning electron micrographs revealed that the nanoparticles could have different effects on microfibril formation of PET/PP MFC depending on their concentration. Addition of appropriate content of nanoparticles (e.g., 1.6 and 8 wt%) facilitated the PET droplet‐fibril transition during stretching due to the presence of nanosilica in the PP matrix, which increased the viscosity of PP matrix and then improved the droplet deformability. However, at higher loading (e.g., 12 wt%), the aggregation of silica nanoparticles around the PET droplets prevented disperse phase coalescence during drawing and then reduced the fibrillation ability of PET minor phase. The dynamic rheological test performed at 190°C showed that the increased spatial restriction of the nanoparticles improved the viscoelastic moduli and complex viscosity of PET/PP MFC. DSC results indicated that nanosilica had little heterogeneous nucleation effect on the PP matrix of PET/PP MFC. Additionally, nanoparticles could present drastic improvement in the degradation behavior of PET/PP MFC under thermo‐oxidative conditions and increased the modulus of PET/PP MFC. POLYM. COMPOS., 38:2718–2726, 2017. © 2015 Society of Plastics Engineers